Evaluation of some commercial dairy rations in terms of chemical composition, methane production, metabolisable energy and organic matter digestibility: Evaluation of some commercial dairy rations - Boga, Mustafa; Kurt, Ozer; Ozkan, Cagri Ozgur; Atalay, Ali İhsan and Kamalak, Adem (Progress in Nutrition, 2020)
The aim of the present study was to evaluate some commercial dairy rations in terms of chemical composition, methane production, net energy for lactation (NEL) and organic matter digestibility (OMD). There are considerable variations among total mixed rations (TMRs) used by farms, especially in terms of chemical composition. Crude protein (CP) contents of TMRs ranged from 9.83 to 14.32 %. Acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents of TMRs ranged from 22.79 to 32.32 % and 42.5 to 52.98 % respectively. There are significant differences among TMRs in terms of gas, methane production, NEL and OMD. Gas production ranged from 82.25 to 97.25 ml. Gas production, NEL and OMD for TMR 3, 6 and 8 was significantly higher than the others. Methane production (ml) for TMR 8 was significantly higher than that for TMR 7. As a conclusion, TMRs investigated in the current study are not well balanced to meet the nutritional requirements of lactating cows. Therefore, it is not likely that lactating cows fed with these TMR will not explain their genetic potential very well. Especially CP and NEL of TMRs should be taken into consideration to improve efficiency in milk production of lactating cows in small farms in Turkey.